Reduction in Clinical Variance Using Targeted Design Changes in Computerized Provider Order Entry (CPOE) Order Sets - Jacobs, B. R.; Hart, K. W.; Rucker, D. W. (Applied Clinical Informatics, 2012)
Objectives: Unwarranted variance in healthcare has been associated with prolonged length of stay, diminished health and increased cost. Practice variance in the management of asthma can be significant and few investigators have evaluated strategies to reduce this variance. We hypothesized that selective redesign of order sets using different ways to frame the order and physician decision-making in a computerized provider order entry system could increase adherence to evidence-based care and reduce population-specific variance.Patients and Methods: The study focused on the use of an evidence-based asthma exacerbation order set in the electronic health record (EHR) before and after order set redesign. In the Baseline period, the EHR was queried for frequency of use of an asthma exacerbation order set and its individual orders. Important individual orders with suboptimal use were targeted for redesign. Data from a Post-Intervention period were then analyzed.Results: In the Baseline period there were 245 patient visits in which the acute asthma exacerbation order set was selected. The utilization frequency of most orders in the order set during this period exceeded 90%. Three care items were targeted for intervention due to suboptimal utilization: admission weight, activity center use and peak flow measurements. In the Post-Intervention period there were 213 patient visits. Order set redesign using different default order content resulted in significant improvement in the utilization of orders for all 3 items: admission weight (79.2% to 94.8% utilization, p<0.001), activity center (84.1% to 95.3% utilization, p<0.001) and peak flow (18.8% to 55.9% utilization, p<0.001). Utilization of peak flow orders for children ≥8 years of age increased from 42.7% to 94.1% (p<0.001).Conclusions: Details of order set design greatly influence clinician prescribing behavior. Queries of the EHR reveal variance associated with ordering frequencies. Targeting and changing order set design elements in a CPOE system results in improved selection of evidence-based care.
Keywords: Asthma; children; CPOE; decision support; framing; heuristic; order sets